The capitalization of non-market attributes into regional housing rents and wages: Evidence on German functional labor market areas - Norbert Hiller; Oliver Lerbs (Westfälische Wilhelms-Universität Münster, Centrum für Angewandte Wirtschaftsforschung (CAWM), 2014)
This paper extends existing research on regional quality of life in Germany by newly estimating the role of region-specific (dis-)amenities in the determination of regional housing rents and wages. Different from previous studies, the empirical analysis draws on functional labor market areas recently delineated by Kosfeld and Werner [Raumf Raumordn (2012) 70: 49-64] rather than administrative jurisdictions, circumventing problems of spatial autocorrelation. Consistent with cross-region spatial equilibrium, the results indicate that labor market area heterogeneity in housing rents and wages is closely related to differences in non-market attributes that affect household utility. The results enable the construction of a comprehensive ranking of regional quality of life which can be directly compared to the findings of previous studies.
Keywords: R13; R21; R23; 330; Functional labor market areas; Non-market (dis-)amenities; Spatial equilibrium analysis; Quality of Life; Spatial autocorrelation